Practical Tools for Patient-specific Characterization and Dosimetry of Radiopharmaceutical Extravasation. Issue 5 (15th July 2022) - Wilson, Sean; Osborne, Dustin; Long, Misty; Knowland, Josh; Fisher, Darrell R.
Abstract: Extravasation during radiopharmaceutical injection may occur with a frequency of more than 10%. In these cases, radioactivity remains within tissue and deposits unintended radiation dose. Characterization of extravasations is a necessary step in accurate dosimetry, but a lack of free and publicly available tools hampers routine standardized analysis. Our objective was to improve existing extravasation characterization and dosimetry methods and to create and validate tools to facilitate standardized practical dosimetric analysis in clinical settings. Using Monte Carlo simulations, we calculated dosimetric values for sixteen nuclear medicine isotopes: 11 C, 64 Cu, 18 F, 67 Ga, 68 Ga, 123 I, 131 I, 111 In, 177 Lu, 13 N, 15 O, 82 Rb, 153 Sm, 89 Sr, 99m Tc, and 90 Y. We validated our simulation results against five logical alternative dose assessment methods. We then created three new characterization tools: a worksheet, a spreadsheet, and a web application. We assessed each tool by recalculating extravasation dosimetry results found in the literature and used each of the tools for patient cases to show clinical practicality. Average variation between our simulation results and alternative methods was 3.1%. Recalculation of published dosimetry results indicated an average error of 7.9%. Time required to use each characterization tool ranged from 1 to 5 min, and agreement between the three tools was favorable. We improved upon existing methods by creating new tools for characterization and dosimetry of radiopharmaceutical extravasation. These free and publicly available tools will enable standardized routine clinical analysis and benefit patient care, clinical follow-up, documentation, and event reporting.